Assessment of the Health Status of Mussels Mytilus galloprovincialis Along the Campania Coastal Areas: A Multidisciplinary Approach - Carella, Francesca; Aceto, Serena; Mangoni, Olga; Mollica, Maria Pina; Cavaliere, Gina; Trinchese, Giovanna; Aniello, Francesco; De Vico, Gionata (Frontiers in Physiology, 2018)
The bivalve Mytilus galloprovincialis has a broad geographic distribution, constitute an important element in the ecology of coastal waters and also represents a major aquaculture species. In the present work, molecular and tissue biomarkers were examined in mussel populations (M. galloprovincialis) located in four different areas of the coastal water of the Campania Region. During an annual life cycle, we analysed the expression patterns of several genes commonly used to estimate cellular stress response and damage, namely p53, p63, HSP70, MT-10 and MT-20, related tissue lesions (pathogens, inflammations, digestive tubules damage), oxidative stress indicators (H2O2, SOD specific activity) and associated environmental data. The computed Principal Component Analysis showed the sampling sites were clearly distinguishable based on the environmental data and biomarker responses. About animal health status, mussels from Gulf of Pozzuoli and Naples’s harbour did exhibit a reduced epithelial cell height compared to mussels sampled from other sampling sites; moreover, high prevalence of cases of intersex in three of the examinated areas were observed. The presence of a potential zoonotic pathogen (Nocardia crassostreae) was identified, appearing as an important possible emerging disease. We also reported the OIE notifiable protozoa Marteilia refringens in three areas out of four. The likely impact of both observed pathogens on the mussel health and shellfish aquaculture needs to be urgently addressed. Results are discussed considering animal histopathological health parameters and biological effects.